The Effect of Road Infrastructure, Foreign Investment, and Tax Revenue on Indonesia: ARDL Model Approach - Fitri Azzahro; Wenny Restikasari (Jurnal Ekonomi Pembangunan, 2025)
This study aims to analyze the short- and long-term effects of road infrastructure, foreign investment, and tax revenue on Indonesia's economic growth, covering the period from 2014Q1 to 2022Q4. The study uses the Autoregressive Distributed Lag (ARDL) model to show that road infrastructure has negative short- and long-term effects. While foreign investment has a positive, insignificant impact in the long term, it can have a positive, significant impact in the short term. Tax revenue has negligible, positive implications only in the long term, but a positive, significant impact in the short term. Based on these findings, the government should prioritize developing and maintaining infrastructure that connects production areas with market centers, industrial areas, and ports, with a focus on integrating different modes of transport. Additionally, offering suitable tax incentives could encourage partnerships between foreign investors and local industries, thereby boosting innovation, production capacity, and technology transfer to promote sustainable economic growth.